High levels of endothelial progenitor cells and circulating endothelial cells in patients with Behçet's disease and their relationship to disease activity - Deniz Aksu Arica; Burak Akşan; Asim Örem; Buket Akcan Altinkaynak; Savaş Yayli; Mehmet Sönmez (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Behçet's disease is a multisystemic vasculitis, associated with vascular endothelial dysfunction. Currently, the prognosis is unpredictable, because there is still no valid laboratory marker indicating the disease activity in Behçet's disease. Endothelial progenitor cells and circulating endothelial cells are newly introduced hematological markers which are presumed to take part in the pathogenesis of vasculitis. Objectives: To evaluate the levels of endothelial progenitor cells and subtypes and circulating endothelial cells in patients with Behçet's disease and to describe their relationship with the disease activity. Methods: A total of 45 patients with Behçet's disease and 28 healthy controls were included in the study. Endothelial progenitor cells (CD34+CD133+KDR+ as early endothelial progenitor cells and CD34+KDR+ as late endothelial progenitor cells), and circulating endothelial cells (CD34+CD133+) were measured by flow cytometry. Results: The mean plasma level of endothelial progenitor cells and circulating endothelial cells, vascular endothelial growth factor, matrix metalloproteinase-9, C-reactive protein, and erythrocyte sedimentation rate were significantly higher in patients with Behçet's disease. All of these parameters except circulating endothelial cells were also found to be higher in patients with active disease than in patients with inactive disease. Early endothelial progenitor cells showed significant correlations with C-reactive protein and circulating endothelial cells. Study Limitations: The cross-sectional nature of the study and patient characteristics such as being under treatment, which can affect endothelial progenitor cells numbers. Conclusion: The increase in endothelial progenitor cells may play an essential role in the repair of endothelial injury in Behçet's disease, especially in the active period of the disease. Thus, endothelial progenitor cells can indicate the disease activity. In addition, endothelial progenitor cells and circulating endothelial cells can be used as endothelial repair and injury markers for Behçet's disease, respectively.